2014
DOI: 10.1186/bf03351767
|View full text |Cite
|
Sign up to set email alerts
|

Pole orientation and triaxial ellipsoid shape of (25143) 1998 SF36, a target asteroid of the MUSES-C* mission

Abstract: The near-earth asteroid (25143) 1998 SF36 is a target body for the Japanese sample-return MUSES-C mission. We present here its pole orientation and triaxial ellipsoid shape, using light curve data obtained with three telescopes at Kiso, Mitaka, and Pic du Midi. The solution obtained for the pole orientation has ecliptic latitude λ = 320 ± 30• and ecliptic longitude β = −75 ± 12• . The estimated triaxial ellipsoid shape is a/b = 2.1 and b/c = 1.7 assuming m = 0.03, which is the coefficient of the empirical rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…From ground-based observations, Itokawa is categorized as an S(IV)-type or Q-type asteroid, which is thought to be similar to ordinary chondrite meteorites (Binzel et al 2001; see also Dermawan et al 2002;Ishiguro et al 2003;Lowry et al 2005;Lederer et al 2005;Cellino et al 2005). The size (535 × 294 × 209 m), rotational spin (retrograde pole with the rotational period of ~12.132 h) and mass density (1.9 g cm −3 ), which was determined by the Hayabusa observations Abe et al 2006b), are in good agreement with the values predicted from the ground-based observations (Kaasalainen et al 2003;Ostro et al 2004; see also Ohba et al 2003;Müller et al 2005;Sekiguchi et al 2003).…”
Section: Introductionsupporting
confidence: 74%
“…From ground-based observations, Itokawa is categorized as an S(IV)-type or Q-type asteroid, which is thought to be similar to ordinary chondrite meteorites (Binzel et al 2001; see also Dermawan et al 2002;Ishiguro et al 2003;Lowry et al 2005;Lederer et al 2005;Cellino et al 2005). The size (535 × 294 × 209 m), rotational spin (retrograde pole with the rotational period of ~12.132 h) and mass density (1.9 g cm −3 ), which was determined by the Hayabusa observations Abe et al 2006b), are in good agreement with the values predicted from the ground-based observations (Kaasalainen et al 2003;Ostro et al 2004; see also Ohba et al 2003;Müller et al 2005;Sekiguchi et al 2003).…”
Section: Introductionsupporting
confidence: 74%
“…The above papers corroborate S-type taxonomic classification (with somewhat higher albedo than for typical S-class asteroids). Ohba et al (2003) found a pole solution similar to ours and concluded that the role played by the surface roughness can have an effect on the inferred relative shape dimensions such as the degree of the flattening of the body. As discussed in Torppa et al (2003), tight constraints for these dimensions require numerous accurate observations with absolute photometry (and may even then remain ambiguous due to the scattering law), so they are probably better obtained with complementary data.…”
Section: Modelmentioning
confidence: 56%
“…Needless to say, Itokawa has been the target of extensive ground-based observational activities, including photometric, spectroscopic and radar observations (Binzel et al, 2001a(Binzel et al, , 2001bDermawan et al, 2002;Abe et al, 2002;Ohba et al, 2003;Lederer et al, 2005;Ostro et al, 2004). These observations have led to derive reliable measurements of the overall shape, spin properties, taxonomic classification, and brightnessphase curve of this asteroid.…”
Section: Introductionmentioning
confidence: 95%